2022
DOI: 10.3390/antibiotics11020175
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Knowledge, Attitudes, Behaviors and Information Sources on Antibiotic Use and Resistance in Jordan

Abstract: Antimicrobial resistance (AMR) is a serious healthcare problem that affects public health globally. Appropriate understanding and knowledge of prudent antimicrobial use and resistance, along with providing evidence-based information sources, are needed for informed antibiotic prescribing practices. This study aimed to assess the knowledge, opportunity, motivation, behavior of pharmacists and their information sources regarding antibiotic use and resistance in Jordan. An online cross-sectional questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
4
16
1
Order By: Relevance
“…Moreover, it was observed that more female pharmacists responded to the survey. This was also similarly observed in other recent surveys [ 42 ]. Moreover, many of the responses on the Likert scale questions were uncertain or sometimes, which might decrease the assurance of the actual responses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, it was observed that more female pharmacists responded to the survey. This was also similarly observed in other recent surveys [ 42 ]. Moreover, many of the responses on the Likert scale questions were uncertain or sometimes, which might decrease the assurance of the actual responses.…”
Section: Discussionsupporting
confidence: 91%
“…Tis fnding further emphasizes the pharmacists' perception of their contribution to the problem and their approval of the importance of laws and proper enforcement of legislations. Tis role is indeed recognized by pharmacists themselves in several studies [20,41,42].…”
Section: Discussionmentioning
confidence: 96%
“…It might be the first pilot study done at the Primary Healthcare Center because most previous studies were conducted at hospitals or community pharmacies. [9][10][11][12][13][14][15][16][17] The reliability test was medium, related to a small sample of participants.…”
Section: Discussionmentioning
confidence: 99%
“…25 The results showed inadequate knowledge of responders with various elements such as antibiotics could be viral or fungal infections or usage for common cold or cough and pain and general inflammation that resemble of had been reported in previous studies 24,26 and differed from other. 14,15 The pharmacy staff is expected to be a significant barrier that prevents reaching wrong medical therapy to patients, which requires a certain level of knowledge that enables them to filtrate prescriptions and catch up on any medication error committed by prescribers. However, having pharmacy staff with deficient knowledge in differentiating antivirals and anti-fungals from antibiotics is disappointing since such information is fundamental in medical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation